AERODYNAMIC CHARACTERISTICS OF AIRFOIL USING PANEL METHOD - Junaidin, Buyung (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2016)
Potential flow over an airfoil plays an important historical role in the theory of flight. The governing equation for potential flow is Laplaceâs equation, a widely studied linear partial differential equation. One of Greenâs identities can be used to write a solution to Laplaceâs equation as a boundary integral. Numerical models based on this approach are known as panel methods in the aerodynamics community. This paper introduces the availability of a computational tool for constructing numerical modelfor potential flow over an airfoil based on panel methods. Use of the software is illustrated by implementing a specific model using Hess and Smith panel method to compute the flow over a member of the NACA four-digit airfoils.